Impacts of Nutritional Management During Early Postnatal Life on Long-Term Physiological and Productive Responses of Beef Cattle - Harvey, Kelsey M.; Cooke, Reinaldo F.; Moriel, Philipe (Frontiers in Animal Science, 2021)
Effective early postnatal nutritional management is a crucial component of livestock production systems, and nutrient manipulation during this period has been shown to exert long-term consequences on beef cattle growth and physiology. Metabolic imprinting defines these biological responses to a nutritional intervention early in life that permanently alter physiological outcomes later in life. Early weaning has been used to study metabolic imprinting effects, given that it allows for nutritional manipulation of animals at a young age. This practice has been shown to enhance carcass characteristics in feedlot cattle and accelerate reproductive development of females. Another strategy to study the effects of metabolic imprinting without the need for early weaning is to provide supplements via creep feeding. Providing creep feed to nursing cattle has resulted in transient and long-term alterations in cattle metabolism, contributing to increased reproductive performance of developing heifers and enhanced carcass quality of feeder cattle. Collectively, results described herein demonstrate nutrient manipulation during early postnatal life exerts long-term consequences on beef cattle productivity and may be a strategy to optimize production efficiency in beef cattle systems.